PENGARUH PENGGUNAAN FERMENTASI CAMPURAN BUNGKIL INTI SAWIT DAN ONGGOK DALAM PAKAN FORMULASI PADA AYAM PEDAGING DENGAN PENAMBAHAN MENGKUDU TERHADAP KONSUMSI PAKAN, PERTAMBAHAN BOBOT BADAN, KONVERSI PAKAN DAN EFISIENSI PENGGUNAAN PAKAN - Jondani, Debi (Universitas Kanjuruhan Malang, 2013)
The aim of this reserch was to know the effect of adding fermentation of cassava waste and palm carnel cake which is adding with extract Morinda Citrifolia in formulation feed of broiler to feed consumption ,body weight gain, feed conversion, and efficiency of feed using. Materials were used in this reserch are 96 broiler chickens unsexed which is produced by PT Japfa Compeed Indonesia tbk. Methodology used in this reserch is experiment by using complete random with 8 treatment, those are P0M0 (feed 100%), P1M0 (feed+10% fermentation ), P2M0 (feed+20% fermentation) P3M0 (feed +30% fermentation ) And by Morinda Citrifolia that is P0M1 (feed + Morinda Citrifolia) P1M1 (feed + morinda citifolianin +10% fermentation) P2M1 (feed + Morinda Cirtifolia +20% fermentation) P3M1 (feed + Morinda Citrifolia +30% fermentation).And each treatmens are repeared 3 times. Each treatment consis of a chickens. The summary of tonglusion using fermentation of palm core bis and cassava waste in formulation feed to chickens which is combined with extract morinda citifolianin does not give real effect to feed consumption , but give real effect for adding of the chickens weight feed converesion and efficiency in using feed of the chickens. There were no significan effect of using feed consumption, while very significan on body weight gain, feed conversion and feed efficiency. It could be suggested to incerese level fermented palm carnel cake and Morinda Cirtifolia extract in broiler Key words : Fermentation, palm carnel cake, cassava waste, Morinda Citrifolia, and Broiler